First record of the genus Dictyopharina Melichar, 1903 (Hemiptera: Fulgoroidea: Dictyopharidae) from China, with descriptions of two new species - Song, Zhi-Shun; Liang, Ai-Ping (Zootaxa, 2006)
The genus Dictyopharina Melichar, 1903, and its type species, D. viridissima Melichar, 1903 from Sri Lanka and India, are redescribed and illustrated. Two new species, D. octaprotrusa sp. nov. and D. sichuanensis sp. nov., are added to the genus from southern China, and they represent the first record of the genus from China. A key to the species of Dictyopharina is provided.